The Determination of Village Area in Semarang Regency Using The Circle Method - Vikky Aprelia Windarni; Adi Setiawan (Universitas Mercu Buana Yogyakarta, 2021)
This research conducted a calculation of all villages area (253 villages) which located in Semarang regency. The data obtained is based on the data from GADM and Google earth by using the coordinate points (latitude and longitude). The research stage used were (1) finding the coordinate of villages boundaries in Semarang regency based on the data from GADM and Google Earth, (2) calculating the village area using two methods (Karney polygon method and circle method) and (3) analyzing the comparison of villages area based on each district and the reference area from Central Statistics Agency (BPS). The purpose of this research is the researchers would like to find out whether or not the Karney polygon method can be used to calculate the area of 253 villages in Semarang regency. From this research, it obtains the percentage difference with the lowest and highest percentage based on the data from GADM and Google Earth. The lowest percentage uses the Karney polygon method (GADM) of 7.63% and the highest percentage is 66.5%. The lowest percentage uses the circle method (GADM) is 14.39% and the highest percentage is 74.79%. The lowest percentage uses the Karney polygon method (Google Earth) is 7.63% and the highest percentage is 66%. The lowest percentage uses the circle method (Google Earth) is 15.87% and the highest percentage is 234%. MdAPE results for the data based on GADM using the Karney polygon method has the percentage of 18.73% and 35.19% by using the circle method. Based on Google Earth using the Karney polygon method, it has the percentage of 18.48% and 33.93% by using the circle method. It can be concluded that the Karney polygon method can be used to calculate the area of 253 villages in 19 districts in Semarang regency based on the data from GADM and Google Earth